LASER ELEMENTAL ANALYZER LASER-Z FOR SOILS, ORES, MINERALS AND MINING AND CHEMICAL RAW MATERIAL - E. Skorina (Минералогия)
SciAsp Company, a leading world producer of portable analytical equipment, presents new series of laser analyzers Laser-Z. Portable mining and geological analyzers Laser-Z will perform field elemental analysis for almost any group of the Periodic Table.